(untitled) (Research, Society and Development, 2023)
The aim of this study was to quantitatively compare type I and type III collagen fibers in histological evaluation of the proximal insertion of the third interosseous muscle (P.I.I.M III) of healthy Crioulo (n=26) and Thoroughbred (n=6) horses, with a mean age of 5.7 years. The histological sections were stained with picrosirius red and examined under an optical microscope under polarized light. Images of 5 fields were captured from each slide at 10x magnification. The percentage of the area occupied by each type of collagen was determined by the threshold color plugin of the Image J software, through analysis of the color segmentation. Nevertheless, the analysis of variance is not demonstrating the significantly variations of the proportion of type I and type III collagen in I.P.M.I III of the evaluated breeds. However, there was a significant difference between the two types of collagens in the same breed, because that type I collagen prevailed over the type III.